Survival among women with cancer of the uterine cervix: influence of marital status and social class. Issue 4 (December 1990) - Murphy, M; Goldblatt, P; Thornton-Jones, H; Silcocks, P
Abstract : STUDY OBJECTIVE--The aim was to investigate whether the survival of women with cancer of the uterine cervix is associated with their marital status and social class. DESIGN--The study was a survey of survival up to 5 years from diagnosis of women with cancer of the cervix registered in the South Thames Cancer Registry, using Cox regression to adjust for marital status, social class, age, and stage at registration. Because of deficiencies in social class data held by the Registry (social class was assigned in only 51% of cases, as opposed to 93% for marital status), the findings were compared with survival data from the OPCS Longitudinal Study. SETTING--During the period of study (1977-81) the South Thames Cancer Registry covered a female population of about 3.5 million in the south east of England. PATIENTS--Data on 1728 women were analysed. MEASUREMENTS AND AND MAIN RESULTS--Apparent differences in crude survival by marital status and social class were examined. These were found to be accounted for by adjustment for age and stage. The better survival of those whose social class was unknown was found to be an artefact of the way in which cancer registries assign social class, but this did not appear to bias registry based studies of social class survival seriously. CONCLUSIONS--(1) After adjusting for age, factors affecting survival in women with cancer of the cervix, such as stage at presentation or host resistance, appear to be similarly distributed in the different marital status and social class groups; (2) for cervical cancer, the marked social class gradient and unusual marital status distribution found in cross sectional mortality data reflect the incidence of the disease, not differences in survival; (3) explanations for these patterns in incidence and mortality data are to be found in the aetiology of the disease.